Sprache intermedial. Stimme und Schrift, Bild und Ton - Linke, Angelika (Jahrbuch des Instituts für Deutsche Sprache, 2010)
In our modern society with its increasing differentiation in culture and media, language and speech are also confronted with new demands and contexts for their use. In the new media, text and image become increasingly closely interwoven, and what were traditionally thought to be firm boundaries between the material forms of language - between speech and writing - appear as increasingly fluid. The volume deals with the diversity of manifestations of our language and its intermedial relations with other forms of communication, including images, body language, sounds, and music.